2011
DOI: 10.1016/j.yjmcc.2011.05.017
|View full text |Cite
|
Sign up to set email alerts
|

Bi-modal dose-dependent cardiac response to tetrahydrobiopterin in pressure-overload induced hypertrophy and heart failure

Abstract: The exogenous administration of tetrahydrobiopterin (BH4), an essential cofactor of nitric oxide synthase (NOS), has been shown to reduce left ventricular hypertrophy, fibrosis, and cardiac dysfunction in mice with pre-established heart disease induced by pressure-overload. In this setting, BH4 re-coupled endothelial NOS (eNOS), with subsequent reduction of NOS-dependent oxidative stress and reversal of maladaptive remodeling. However, recent studies suggest the effective BH4 dosing may be narrower than previo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 33 publications
1
30
0
Order By: Relevance
“…Pharmacological supplementation of BH4 improves endothelium-dependent relaxation and NOS coupling (155,157). BH4 aids electron transfer from the NOS reductase to the oxidase domains, assisting in the production of NO and L-citrulline from L-arginine.…”
Section: Nos Recouplersmentioning
confidence: 99%
See 1 more Smart Citation
“…Pharmacological supplementation of BH4 improves endothelium-dependent relaxation and NOS coupling (155,157). BH4 aids electron transfer from the NOS reductase to the oxidase domains, assisting in the production of NO and L-citrulline from L-arginine.…”
Section: Nos Recouplersmentioning
confidence: 99%
“…Another factor is that orally consumed BH4 is rapidly oxidized, and should be reconverted by DHFR to be effective. Even in mice, where exogenous BH4 is effective for treating heart disease, increasing the dose led to a paradox reversal of benefit, re-appearance of ROS, and this was coupled with a decline in the BH4/BH2 ratio toward baseline (155). Variability in both uptake and redox modification of exogenous BH4 depending on the patient and disease would greatly complicate its clinical pharmacology.…”
Section: Nos Recouplersmentioning
confidence: 99%
“…Additionally, the exogenous administration of the NOS cofactor BH4 has been shown to reduce LV hypertrophy, fibrosis and cardiac dysfunction in mice with pre-established pressure overload. In this setting, BH4 recoupled endothelial NOS, with subsequent reduction of NOS-dependent oxidative stress and reversal of maladaptive remodeling [195,196].…”
Section: K1c Ratmentioning
confidence: 99%
“…Malo et al (11) reported that treatment with BH4 prevented endothelial dysfunction in epicardial coronary arteries associated with left ventricular hypertrophy in a porcine model. Moreover, administration of BH4 has been shown to protect the myocardium against pressure overload, resulting in the improvement of fibrosis, cardiac dysfunction and hypertrophy (12)(13)(14). Takimoto et al (15) showed that pressure overload triggers NOS3 uncoupling as a prominent source of myocardial ROS contributing to dilatory remodeling and cardiac dysfunction using NOS3-deficient mice.…”
Section: Introductionmentioning
confidence: 99%